Annular Structural Colors from Bowl‐Like Shriveled Photonic Microshells of Cholesteric Liquid Crystals. Issue 20 (5th August 2020) - Shan, Yu‐Wei; You, Lu‐Qian; Bisoyi, Hari Krishna; Yang, Yu‐Jie; Ge, Ya‐Hao; Che, Kai‐Jun; Li, Sen‐Sen; Chen, Lu‐Jian; Li, Quan
Abstract: Structural colors obtained by self‐organized microstructures have found a variety of applications, such as decorations, displays, and encryption microarrays, and have been widely investigated for the excellent stability and anisotropic optical responses upon external stimuli. Here, the fabrication of a variety of bowl‐like shriveled microshells using helical cholesteric liquid crystals (CLCs) by glass‐capillary‐based microfluidic techniques is reported. Interestingly, the internal and selective Bragg interferences of the radially arranged helical CLC structure enable the color‐correlative optical responses, resulting in the generation of annular color rings with variable reflection wavelengths and geometries by tuning the pitch and adjusting the incubation parameters. In addition, the manipulation of shriveled photonic microshells is demonstrated under a magnetic field. Benefiting from the low‐cost fabrication of optical interference microstructures and the controllable generation of structural color, it is expected that this class of shriveled photonic CLC microshells might pioneer a novel route for future photonic applications and beyond. Abstract : A variety of bowl‐like shriveled microshells with helical cholesteric liquid crystals (CLCs) is fabricated by glass‐capillary‐based microfluidic techniques. The internal and selective Bragg reflections of 1D helical CLC structures enable color‐correlative optical responses, resulting in the generation of annular structural colors with variable reflection wavelengths and shapes by tuning the pitch and adjusting osmotic pressure.